Evaluation of AFP Surveillance Sensitivity in AJK (Medical Forum Monthly, 2024)
Objective: Main objective of the study is to analyse sensitivity of the surveillance system, required to keep poliovirus circulation ceased in AJK.Study Design: Retrospective analysis of AFP cases reported during the study period. Place and Duration of Study: This study included all the AFP cases reported during the study period in AJK from Jan. 2011 to Dec. 2013.Materials and Methods: Historical data is used to analyse AFP surveillance for detecting poliovirus infection in children age <15 years in the study area based on few assumptions that all the results are negative and adequate information were available to make ultimate diagnosis of each AFP case reported in the area during study period. Surveillance sensitivity analysed using AFP surveillance criteria recommended by WHO and variable used in AFP surveillance system.Results: Surveillance sensitivity is analysed based on two indicators “non polio AFP rate” and stool adequacy. Sensitivity level analysed in AFP cases aged 6-59 months for ≥7 OPV doses including routine and SIAs revealed 6/10 districts have high sensitivity. Conclusion: Long absence of Polio virus in the area, creeping up of boredom among health human resource, Clinician’s failure to notify all AFP cases resulting in down going Surveillance sensitivity.